Communication skills among different classroom management styles teachers / Teoh Sian Hoon, Nur Fadzlin Mohamad Nasaruddin and Parmjit Singh - Teoh, Sian Hoon; Mohamad Nasaruddin, Nur Fadzlin; Singh, Parmjit (Penerbit UiTM (UiTM Press), 2017)
The significance put in refining communication skills among teachers plays a central role in connecting students' various knowledge. With that, classroom management styles with good communication skills become a major focus in achieving fundamental educational aims. Unfortunately, communication skills and management styles for classroom learning are always seen as isolated components. Hence, this study aims to investigate the communication skills used among teachers with different classroom management styles in Malaysia primary schools. This study attempts to achieve four objectives; namely, to examine the teachers' level of communication skills in listening, ability to get message across, emotional management in the communication process, insight to the communication process and assertive communication; to investigate level of communication skills between male teacher and female teacher; to describe the percentages of the teachers with different classroom management styles; and to investigate the level of communication skills between different classroom management styles. This study employed the survey causal comparative research design that focuses on the quantitative approach. The respondents of this study were 70 primary school teachers who were randomly selected in the area of Perak, Malaysia. A questionnaire was administered in this survey with results showing that the teachers have their personal set of communication skills with different classroom management styles. Nevertheless, the analysis showed that there is no strong evidence that there is a significant difference in the communication skills based on gender. Results also revealed that there is a significant difference in communication skills between the two different categories of classroom management styles.